2015
DOI: 10.1016/j.bone.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Muscle volume is related to trabecular and cortical bone architecture in typically developing children

Abstract: Introduction Muscle is strongly related to cortical bone architecture in children; however, the relationship between muscle volume and trabecular bone architecture is poorly studied. The aim of this study was to determine if muscle volume is related to trabecular bone architecture in children and if the relationship is different than the relationship between muscle volume and cortical bone architecture. Materials and methods Forty typically developing children (20 boys and 20 girls; 6 to 12 y) were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Regarding the relationship between BUA and lean body mass, several studies examining factors affecting BUA during adolescence showed results similar to those of this study (Correa-Rodríguez, Rio-Valle, González-Jiménez, & Rueda-Medina, 2016;Zulfarina et al, 2018). Muscle mass in the midthigh has a moderate to strong positive correlation with trabecular bone architecture (Bajaj et al, 2015). According to mechanostat theory, increased muscle mass produces a stimulus for increased bone mass (Rauch, Bailey, Baxter-Jones, Mirwald, & Faulkner, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the relationship between BUA and lean body mass, several studies examining factors affecting BUA during adolescence showed results similar to those of this study (Correa-Rodríguez, Rio-Valle, González-Jiménez, & Rueda-Medina, 2016;Zulfarina et al, 2018). Muscle mass in the midthigh has a moderate to strong positive correlation with trabecular bone architecture (Bajaj et al, 2015). According to mechanostat theory, increased muscle mass produces a stimulus for increased bone mass (Rauch, Bailey, Baxter-Jones, Mirwald, & Faulkner, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, higher muscle perimeters are associated with higher calcaneus stiffness. A recent study reported that midthigh muscle volume is moderately-to-strongly related to trabecular bone architecture [ 44 ]. In our study and others, the association between muscle mass and bone parameters is consistent in both sexes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A strong positive-association between bone mass and muscle mass throughout life has been attributed to their shared function (1)(2)(3)(4)(5). This mechano-functional theory has been built upon studies using different approaches.…”
Section: Introductionmentioning
confidence: 99%